Enzymes in Winemaking: Harnessing Natural Catalysts for Efficient Biotransf ormations - A Review - van Rensberg, P.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2019)
Enzymes play a definitive role in the ancient and complex process of winemaking. From a scientific and technical point of view, wine can be seen as the product of enzymatic transformation of grape juice. From the pre-fermentation stage, through fermentation, post-fermentation and aging, enzymes are the major driving forces catalysing various biotransformation reactions. These biocatalysts originate not only from the grape itself but also from yeasts and other microbes (fungi and bacteria) associated with vineyards and wine cellars. Through better understanding of these enzymatic activities, winemakers have come to learn how to control the unwanted enzymes while optimising the desired activities. Today, winemakers reinforce and extend the action of these endogenous enzymes by the judicious application of an ever-increasing spectrum of commercial enzyme preparations. These enzyme preparations are applied to winemaking with the aims of improving the clarification and processing of wine, releasing varietal aromas from precursor compounds, reducing ethyl carbamate formation and lowering alcohol levels. This review article summarises the most important enzymes applied to winemaking, the nature and structure of their substrates, and the reactions catalysed by these enzymes. This paper also reviews the limitations of the endogenous enzymes derived from grapes and microbes present in must and wine, along with the effects of commercial enzyme preparations on process technology and the quality of the final product. Prospects of developing wine yeast strains expressing tailored enzymes are also highlighted.